Keputusan Penganggaran Modal Pada Usaha Mikro Kecil Menengah Atau Umkm Toko Sepatu Wak Ndut di Laut Dendang Simpang Beo - Harahap, Lokot Muda; Yuliarman, Putri; Ramadhani, Dilla Amelia; Baihaqi, Muhammad; Nasution, Muhammad Ikrom (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The importance of budgeting in a business is to know whether the business is running well or not, with the business running well it will make it easier for MSMEs to continue to soar forward so that they can provide benefits to the surrounding area where the MSMEs are located, such as the Wak Ndut Shoe Shop business in Laut Dendang. In this research, the author conducted direct interviews with the Wak Ndut Shoe Shop MSME business which has developed rapidly in the Dendang Sea. The results of the research show that the Wak Ndut Shoe Shop MSME business is not yet completely perfect because there are many things that are wrong with the Wak Ndut Shoe Shop's budgeting, so evaluation is a good thing for the Wak Ndut Shoe Shop business so that it can develop rapidly in the future.